Impact of COVID-19 pandemic on pediatric cardiac services in India - Mrigank Choubey; Sivasubramanian Ramakrishnan; Sakshi Sachdeva; Kalaivani Mani; Debasree Gangopadhyay; Kothandam Sivakumar; Mahesh Kappanayil; Mahimarangaiah Jayranganath; Nageswara Rao Koneti; Neeraj Awasthy; Prashant Bobhate; Saurabh Kumar Gupta; et al. (Wolters Kluwer Medknow Publications, 2021)
Background : COVID-19 pandemic has disrupted pediatric cardiac services across the globe. Limited data are available on the impact of COVID.19 on pediatric cardiac care in India. Aims : The aims are to study the impact of COVID-19 pandemic on the care of children with heart disease in India in terms of number of outpatient visits, hospitalizations, catheter-based interventions, and cardiac surgeries. Settings and Design : This is a retrospective, multicentric, observational study. Methods : We collected monthly data on the number and characteristics of outpatient visits, hospitalizations, catheter-based interventions, and cardiac surgeries and major hospital statistics, over a period of 5 months (April to August 2020), which coincided with the first wave of COVID-19 pandemic in India and compared it with data from the corresponding months in 2019. Results : The outpatient visits across the 24 participating pediatric cardiac centers decreased by 74.5% in 2020 (n = 13,878) as compared to the corresponding period in 2019 (n = 54,213). The reduction in the number of hospitalizations, cardiac surgeries, and catheterization procedures was 66.8%, 73.0%, and 74.3%, respectively. The reduction in hospitalization was relatively less pronounced among neonates as compared to infants/children (47.6% vs. 70.1% reduction) and for emergency surgeries as compared to elective indications (27.8% vs. 79.2%). The overall in-hospital mortality was higher in 2020 (8.1%) as compared to 2019 (4.8%), with a higher postoperative mortality (9.1% vs. 4.3%). Conclusions : The current COVID-19 pandemic significantly impacted the delivery of pediatric cardiac care across India with two-third reduction in hospitalizations and cardiac surgeries. In an already resource-constrained environment, the impact of such a massive reduction in the number of surgeries could be significant over the coming years. These findings may prove useful in formulating strategy to manage subsequent waves of ongoing COVID-19 pandemic.